A professional virtues-based ethical framework for medical missionsAJOG Global Reports at a Glance - William Onyebeke, MD; Tochi Iroku-Malize, MD; Laurence B. McCullough, PhD; Amos Grünebaum, MD; Frank A. Chervenak, MD (Elsevier, 2021)
BACKGROUND: More than 1.6 million physicians participate in medical missions each year. This effort is part of a long history of volunteerism and service to those in need in the form of medical missions to low-income countries. The Children's Health International Medical Project of Seattle has provided the following 7 guiding principles of sustainable short-term international medical missions: "mission, collaboration, education, service, teamwork, sustainability, and evaluation." The role of professional virtues in grounding these principles and thus guiding medical missions is underappreciated. OBJECTIVE: To provide a professional virtues-based ethical framework for medical missions, this article addressed the question, "How should physicians design and implement a medical mission in a professionally responsible way?" Reference is made to one of the authors' experiences as a point of reference. STUDY DESIGN: The authors addressed the questions on how to design and implement a medical mission based on 5 professional virtues: compassion, integrity, humility, self-effacement, and self-sacrifice. A concise, historically based explanation of each virtue was provided, and the implications of the aforementioned principles for medical missions were identified. RESULTS: Compassion motivates the mission and its team members, whereas integrity, humility, self-effacement, and self-sacrifice guide team members as they act on the professional virtue of compassion. CONCLUSION: These 5 professional virtues can be used to provide a practical framework for the professionally responsible design and implementation of medical missions.